2018
DOI: 10.4306/pi.2018.15.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Resilience on the Association between Emotional Neglect and Depressive Symptoms

Abstract: ObjectivePrevious studies have reported that childhood maltreatment experiences could induce biological and psychological vulnerability in depressive disorders. However, it is still unclear that type-specific effects of childhood maltreatment on psychological resilience, depressive symptoms and interactions among childhood maltreatment experiences, resilience, and depressive symptoms.MethodsA total of 438 medical students were included in the study. The Childhood Trauma Questionnaire-Short Form, the Conner-Dav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Additionally, findings of the study revealed that resilience mediated the effect of meaningful living and affective balance on psychological health among young adults. Consistent with these results, previous research indicated the mediating effect of resilience on psychological health problems in the context of various adverse experiences (e.g., child maltreatment, social exclusion, and stress; Arslan 2016 , 2019 ; Karaırmak and Siviş-Çetinkaya 2011 ; Lee et al 2018 ; Shi et al 2015 ). A meta-analysis study by Hu et al ( 2015 ) revealed that individuals with lower resilience reported greater depression, negative affect, and anxiety, as well as lower positive affect and life satisfaction than those with higher resilience.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, findings of the study revealed that resilience mediated the effect of meaningful living and affective balance on psychological health among young adults. Consistent with these results, previous research indicated the mediating effect of resilience on psychological health problems in the context of various adverse experiences (e.g., child maltreatment, social exclusion, and stress; Arslan 2016 , 2019 ; Karaırmak and Siviş-Çetinkaya 2011 ; Lee et al 2018 ; Shi et al 2015 ). A meta-analysis study by Hu et al ( 2015 ) revealed that individuals with lower resilience reported greater depression, negative affect, and anxiety, as well as lower positive affect and life satisfaction than those with higher resilience.…”
Section: Discussionsupporting
confidence: 75%
“…Because our findings were obtained from studies using the CATS and Japanese subjects, measurement invariance should be confirmed. However, several studies using a different abuse questionnaire (the Childhood Trauma Questionnaire) and subjects of different countries also demonstrated that emotional abuse and neglect have a closer association with depressive symptoms than other types of abuse 32,33. Hence, neglect is considered to be the most influential factor for depressive symptoms among several types of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several negative emotions are commonly self-reported by victims of psychological abuse, including anger, fear, shame, and guilt, which are also common indicators of depression [124]. Empirical research dealing with the consequences of childhood emotional abuse on adult functioning is scarce.…”
Section: Psychological Abusementioning
confidence: 99%